IMPLEMENTASI ALGORITMA DJIKSTRA MENENTUKAN JARAK TERDEKAT JELAMBAR KAMPUS STMIK NUSA MANDIRI CENGKARENG - Musriatun Napiah; Rachma Darma Astuti; Mustofa Mustofa (Akrab Juara : Jurnal Ilmu-ilmu Sosial, 2022)
Traffic jams in Jakarta have become our daily sight. There are many steps that have been taken by the government to solve congestion in Jakarta. However, traffic jams still occur today. The high mobility of road users is often constrained by the lack of limited road facilities and infrastructure. Therefore, road users must find their own way to solve this problem. That is, one of the most effective and efficient ways is to find an alternative route or route for the shortest distance that can be traversed using the Djikstra Algorithm. So that the journey from the Jelambar area to the STMIK NUSA MANDIRI Cengkareng campus can be passed quickly without being blocked by traffic jams. The use of the Djikstra Algorithm can provide a solution because the Djikstra Algorithm provides output in the form of the fastest and shortest path from the place of origin to our destination.